Cell Wall Biomolecular Composition Plays a Potential Role in the Host Type II Resistance to Fusarium Head Blight in Wheat - Lahlali, Rachid; Kumar, Saroj; Wang, Lipu; Forseille, Li; Sylvain, Nicole; Korbas, Malgorzata; Muir, David; Swerhone, George; Lawrence, John R.; Fobert, Pierre R.; Peng, Gary; Karunakaran, Chithra (Frontiers in Microbiology, 2016)
Fusarium head blight (FHB) is a serious disease of wheat worldwide. Cultivar resistance to FHB depends on biochemical factors that confine the pathogen spread in spikes. Breeding for cultivar resistance is considered the most practical way to manage this disease. In this study, different spectroscopy and microscopy techniques were applied to discriminate resistance in wheat genotypes against FHB. Synchrotron-based spectroscopy and imaging techniques, including focal plane array infrared and X-ray fluorescence (XRF) spectroscopy were used to understand changes in biochemical and trace elements in rachis following FHB infection. Sumai3 and Muchmore were used to represent resistant and susceptible cultivars to FHB, respectively, in this study. The histological comparison of rachis showed substantial differences in the cell wall thickness between the cultivars after infection. Synchrotron-based infrared imaging emphasized substantial difference in biochemical composition of rachis samples between the two cultivars prior to visible symptoms; in the resistant Sumai3, infrared bands representing alkyl ester, cellulose and lignin vibrations as well as amide I, pectin, cellulose, hemicellulose, and aromatics group were stronger and more persistent compared to the susceptible cultivar. These bands may be the candidates of biochemical markers for FHB resistance. Focal plane array infrared imaging (FPA) spectra from the rachis epidermis and vascular bundles revealed a new band (1710 cm-1) related to the oxidative stress on the susceptible cultivar only. XRF spectroscopy data revealed differences in trace elemental composition between cultivars, and between non-inoculated and inoculated samples, with substantial increases observed for Ca, K, Mn, Fe, Zn, and Si in the resistant cultivar. These trace elements are related to cell wall stability, metabolic process, and plant defense mechanisms such as lignification pathway and callose deposition. The combination of cell wall elemental composition and lignification plays a role in the mechanism of type II host resistance to FHB. Biochemical profiling using the synchrotron-based spectroscopy holds potential for screening wheat genotypes for FHB resistance.